Superovulation of high-producing Holstein lactating dairy cows with human recombinant FSH and hMG - Khodadadi, Alireza; Niasari-Naslaji, Amir; Nikjou, Darab; Mohammadi, Behrouz (Theriogenology, 2022)
Superovulation of high-producing dairy cows is a challenging subject in dairy farms with respect to the cost, dose and type of gonadotropin. The objectives of this study were to compare three gonadotropin products: Folltropin-V® (highly purified FSH with porcine origin), Cinnal-f® (recombinant human FSH) and Menotropins® (hMG) for superovulation in high-producing Holstein lactating dairy cows and to investigate the pregnancy outcomes achieved following transferring embryos recovered from donors treated with different gonadotropins. Healthy high-producing Holstein lactating dairy cows (n = 30; milk production: 46.35 ± 8.78 kg; parity: 2–4; days in milk: 80–130 days) without any puerperal problems were selected as donors. On Day 10 after estrus (Day 0 of superovulation), donors (10 cows in each experimental groups) received Folltropin-V® (400 mg NIH, dissolved in 20 ml), Cinnal-f® (20 vials; each vial of 1 ml contains 75 IU Follitropin alfa) and Menotropins ® (20 ampules; each ampule of 1 ml contains 75 IU FSH and 75 IU LH), administered twice daily, in decreasing doses (4,4; 3,3; 2,2; 1,1 ml), over 4 days. On Day 2 of superovulation, donors received 3 doses of prostaglandin F2α analogue, 6 h apart. They were inseminated twice with a frozen semen at 12 and 24 h after standing estrus. Concurrent with the second insemination, donors received 2500 IU hCG (Karma Pharmatech GmbH, Germany). On Day 7 after standing estrus, superovulatory responses (number of CLs, total ova/embryos and transferable embryos) were recorded and Code 1 embryos, recovered from each treated donors, were transferred to synchronized heifers. Pregnancy was detected on Day 30 and 60 after AI. Gestation length, the number and weight of live births were recorded. Data were analyzed using Proc GLM, Proc Mixed and Proc Genmod of SAS. The respective number of corpora lutea, total number of ova/embryos and transferable embryos were not different among donors received Cinnal-f (25.5 ± 3.01, 11.2 ± 2.77, 5.1 ± 0.86), Menotropins (24.0 ± 3.21, 9.0 ± 2.04, 6.3 ± 1.74) and Folltropin-V (20.3 ± 3.21, 8.9 ± 1.90, 5.1 ± 1.16; P > 0.05). Pregnancy rates on Day 30 was similar among treatment groups (P > 0.05). However, pregnancy rates on Day 60 and the number of calves born healthy was less in heifers that received embryos from Cinnal-f treated donors (P < 0.05). In conclusion, Cinnal-f and Menotropins could provide similar superovulatory response to Folltropin-V for superovulation of high-producing Holstein lactating dairy cows. •Human recombinant FSH and hMG could be a good gonadotropin candidate for superovulation of high-producing Holstein lactating dairy cows.•Cinnal-f (human recombinant FSH) is a cheap and effective gonadotropin for superovulation in cattle.•The dose and protocol for superovulation of high-producing Holstein lactating dairy cows with Folltropin-V, hMG and Cinnal-f were presented in this manuscript.